MULTIMODAL CONTAINER SCHEMES FREIGHT DELIVERY - Ohiienko, Mykola; Ohiienko, Alona; Bahrii, Mariia (Systems and Technologies, 2022)
Summary. The article highlights the topical issue of development of container multimodal transport, which are a priority in the development of transport services, their use will increase the volume of cargo delivered to the destination by the most efficient modes of transport (their combination). Container transportation of goods significantly reduces the cost of delivery of goods from producers to consumers. Container transportation has become the most economical without transhipment technology, and, above all, in the intercontinental multimodal land-sea service. The aim of the work is to study the practical aspects, substantiate practical recommendations for the logistics of multimodal container transportation of goods in global supply chains. Conduct at comparative analysis of the implementation of multimodal container traffic in different containers, namely 20 and 40 feet. The analysis and calculations of the data of container transportation processes for the conditions of two international transport corridors: TRACECA and trans-Caspian international transport route are carried out. The cost of transportation by sea, although their number is small relative to the total share of routes, significantly affects the total cost of transportation. In order to stimulate freight traffic on these routes, member states have set discounts of up to 10% of the cost of the ferry fare. Studies suggest that the use of multimodal container traffic is currently economically feasible. The conducted research of practical aspects and substantiation of practical recommendations on logistics of multimodal container transportation of goods in global supply chains suggests that the use of container transportation is a way of delivery today using multimodal options for delivery of goods. An in-depth comparative analysis of the implementation of multimodal container traffic in different containers, namely 20 and 40 feet, allows us to conclude that the use of the Trans-Caspian International Transport Route (TMTM) with a 20-foot container is a more economically attractive option and can be recommended.